Effect of Emotional Intelligence on Employee Performance in Almasi Beverages Limited, Kenya - Rono, Leah C; Korir , Michael K.; Boit , Rose J. (African Journal of Education,Science and Technology (AJEST), 2017)
Emotional intelligence is a crucial factor for organization's performance and growth for it plays an important role in performance of today’s competitive organizations and is an essential factor responsible for determining success in one’s life and psychological wellbeing. The study focused on effect of emotional intelligence using Mayer, Salovey & Caruso Emotional Intelligence Tests (MSCEIT) on employee’s performance because little research to date has examined how emotional intelligence affects employees’ performance in a manufacturing setting which this study strives to obtain. Explanatory research design was used with a sample size of 338 employees drawn from the target population of 826 employees of Almasi Beverages Limited. The questionnaires were used for gathering primary data and were administered to the respondents directly by the researcher. The data gathered was analyzed through descriptive statistics such as frequency tables and percentages as well as inferential statistics. Pearson correlation was used to examine the direction and strength of the relationship while multiple regression analysis was used to determine whether independent variable (emotional intelligence) has an effect on dependent variable (employee performance). This study supports Howard and Cropanzano’s Affective Events Theory which links emotional intelligence on employee performance. The results indicate that there is a positive correlation between emotional intelligence and employee performance. (r = .476, p <.001). It is therefore concluded that emotional intelligence affects employee performance hence the researcher recommends emotional intelligence as a tool for policy making, theory development, practice in organizations and further research.